A teoria regional na atualização da Geografia Crítica contemporânea: a urbanização da fronteira na Amazônia, a região do Sul e Sudeste do Pará - Eudes Leopoldo (Confins)
The critical regional theory produced by geography was constituted in France, England and the United States and promoted by groups of scholars linked to a critical perspective of geographical thought. In Brazil, the critical regional theory arrives especially through two exponents: Sandra Lencioni and Rogério Haesbaert. Sandra Lencioni is deeply influenced by the ideas of the French and American schools of geography and Rogério Haesbaert by the English school of geography. Understanding the critical regional theory, which allows us to leave the plane of the region as pure delimitation or clipping of space, thinking of it as a social relation as a concrete abstraction of a differential spatiality, is what drives the interpretation of the urbanization phenomenon in the reproduction of the border region within Amazon, focusing on the network of cities in the emblematic south and southeast of Pará.